2020
DOI: 10.1111/cge.13670
|View full text |Cite
|
Sign up to set email alerts
|

Adult onset tubulo‐interstitial nephropathy in MT‐ND5‐related phenotypes

Abstract: Kidney is a highly adenosine triphosphate dependent organ in human body. Healthy and functional mitochondria are essential for normal kidney function. Clinical and genetic variability are the hallmarks of mitochondrial disorders. We report here the involvement of two MT‐ND5 pathogenic variants encoding for ND5 subunit of respiratory chain complex I, the m.13513G>A and the m.13514A>G, in adult‐onset kidney disease in three unrelated patients. The first patient had myopathy encephalopathy lactic acidosis and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…According to the previously reported cases, kidney involvement with the m.13513G>A/MT-ND5 variant can either manifest as tubulointerstitial kidney disease, sometimes with "secondary" FSGS, or segmental glomerulosclerosis. However, in all cases, glomerular mitochondria were reported to be morphologically normal (Ng et al, 2019;Bakis et al, 2020). Tubular disorders are more common in mitochondrial cytopathies, probably due to the very high metabolic rates and abundant mitochondria in renal tubular cells (Emma and Salviati, 2017).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…According to the previously reported cases, kidney involvement with the m.13513G>A/MT-ND5 variant can either manifest as tubulointerstitial kidney disease, sometimes with "secondary" FSGS, or segmental glomerulosclerosis. However, in all cases, glomerular mitochondria were reported to be morphologically normal (Ng et al, 2019;Bakis et al, 2020). Tubular disorders are more common in mitochondrial cytopathies, probably due to the very high metabolic rates and abundant mitochondria in renal tubular cells (Emma and Salviati, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Remarkably, this pathogenic variant has also been recently described in patients with adult-onset nephropathy (Motoda et al, 2012;Ng et al, 2019;Bakis et al, 2020). Another reported case associated with nephropathy and optic atrophy has been reported (Bakis et al, 2020), with a different nucleotide change, yet affecting the same codon, but leading to a different amino acid substitution (D393G vs. D393N) (Corona et al, 2001). The kidney histology and heteroplasmy were not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 13 , 14 , 15 , 16 , 17 Since 2006, studies have reported that mitochondrial nephropathy is associated with nDNA mutations related to coenzyme Q10 synthesis. 35 , 36 , 37 , 38 , 39 In addition, mtDNA mutations in MT-ATP6 , 40 MT-CO1 , 41 and MT-ND5 , 42 which encode the subunits of complexes I, IV, and V, respectively, have recently been reported. Single and multiple mtDNA deletions owing to nDNA mutations can also cause mitochondrial nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers linking progression of DN with electron ETC identifi ed dysregulated complex I, III, and/or IV activity in mitochondria from either whole diabetic kidney or cortex in a number of established animal models of DN (8,40,41). Mutations leading to compromised complex I function have been demonstrated to contribute to kidney damage in animal models and human pathologies (42,43,44). Whereas complex I activity seemed to be increased in the early phase of DM in some studies (40), a large body of evidence has ultimately shown that complex I, III, and IV activities are reduced as DN progresses (8,41).…”
Section: Kidney Involvement In Mito Point Mutations May Not Be Accomp...mentioning
confidence: 99%